In Vitro Analysis of Cross-Contamination and Disinfection Methods of Prosthetic Components Coming from Laboratories - Braga, Carlos; Rivaldo, Elken Gomes; Paula, Arthur Saavedra de; Bourgi, Rim; Hardan, Louis; Kharouf, Naji; Qaddomi, Mohammad; Haikel, Youssef; Klein-Junior, Celso Afonso (Hygiene (Basel, Switzerland), 2025)
The customization and handling of implant abutments in prosthetic laboratories can lead to microbial contamination, requiring disinfection before clinical use. This study evaluated cross-contamination in abutments from three prosthetic laboratories, identifying microorganisms and assessing the disinfection efficacy of 2% chlorhexidine digluconate (2% CL) and ultraviolet C (UV-C) radiation. Sixty abutments were analyzed, with contamination detected in 83%, predominantly Enterococcus faecalis (34.2%) and Staphylococcus epidermidis (17.8%). Post-disinfection, CFU reduction was 92% (UV-C) and 93% (CL), confirmed by the Wilcoxon test (Z = −4.373; p < 0.001). A comparative analysis using the Kruskal–Wallis test showed no significant difference between the two methods (p > 0.05). These findings confirm that both UV-C and CL effectively reduce microbial load, providing reliable disinfection protocols for clinical practice.